Penyusunan Anggaran Modal Pada UMKM Bakso Kojek Pak Muchlis - Harahap, Lokot Muda; Asyifah Fauzah Delfira; Suci Ramadani; Farhan; Teddy Ramaditya; Dia Ovitri Agustin (Master Manajemen, 2024)
: Budgets can help MSMEs plan activities and expenditures in the future. With a budget, MSMEs can compare expenditures with predetermined plans. The aim of this research is to look at the budget preparation for Bakso Kojek MSMEs. This research uses qualitative descriptive data obtained through interviews and direct observation by researchers. This research was conducted at the Bakso Kojek UMKM on Jl. Wiliam Iskandar, New Memories, District. Percut Sei Tuan, Medan City, North Sumatra, This research was conducted in April 2024.